Adaptive parental effects and how to estimate them: A comment to Bonduriansky and Crean. Issue 3 (6th November 2017) - Engqvist, Leif; Reinhold, Klaus
Abstract: To fully understand the evolution of adaptive parental effects we need to reliably estimate their magnitude. Recently, we (Engqvist & Reinhold, 2016, Methods in Ecology and Evolution, 7, 1482) highlighted some important problems when estimating the magnitude of anticipatory parental effects in the so‐called match/mismatch experiments. As the signature of such parental effects is a statistical interaction between parental environment and offspring environment, it will be difficult to disentangle these effects from other effects depending on a combination of parental and offspring environment, such as context‐dependent silver‐spoon (= condition‐transfer) effects. In a recent article, Bonduriansky and Crean (2017, Methods in Ecology and Evolution ) suggested to manipulate environmental quality on a continuous scale and using a geometric framework as a way out of this dilemma. Here, we highlight and discuss the benefits and potential drawbacks of the suggested method. We conclude that using this approach, one may extract more detailed information but unfortunately, it will not resolve the interpretive ambiguity inherent in this experimental design.